Fabrication of high quality, thin Ge-on-insulator layers by direct wafer-bonding for nanostructured thermoelectric devices. (21st February 2017) - Veerappan, Manimuthu; Mukannan, Arivanandhan; Salleh, Faiz; Shimura, Yosuke; Hayakawa, Yasuhiro; Ikeda, Hiroya
Abstract: A simple means of fabricating thin Ge-on-insulator (GOI) layers with a strong bond at the Ge/SiO2 interface through direct wafer-bonding is described. In this work, high quality Ge/SiO2 bonding was achieved under ambient air and at room temperature as a result of the extremely hydrophilic bonding surfaces obtained by chemical treatment prior to direct bonding. Based on the results of this work, the first-ever bonding mechanism between ammonium hydroxide treated Ge and SiO2 /Si wafer surfaces is proposed. In addition, strain generated during post-annealing as a consequence of the significant thermal-expansion mismatch between Ge and SiO2 was gradually relieved by applying a multistep-cooling process. Structural characteristics of the thin GOI layer were analyzed by cross-sectional scanning electron microscopy, Raman spectroscopy, x-ray diffraction and transmission electron microscopy. It was determined that direct wafer-bonding followed by polishing could produce a GOI layer as thin as 156 nm, with sub-nm surface roughness.